Design of Mobile-Based Geographic Information System Potential of Agricultural Land in Sub-District Completed - Putra Malem Barus (International Journal of Health Engineering and Technology, 2022)
Communication The rapid development of information technology provides tremendous benefits to the community. For this reason, an application is needed to make it easier for people to get information. Various techniques, methods, and new approaches are implemented to improve and develop technology in an effort to obtain fast, precise, and accurate geographic information. A system must have the ability so that the system can be said to be useful for its users. A GIS must have at least four capabilities, namely the ability to manipulate attributes, and the ability to display input and output using images. Mobile applications have a user interface with a unique interaction mechanism provided by the mobile platform. Mobile applications have also been specifically designed for mobile platforms (eg IOS, Android, or Windows Mobile).